THE IMPACT OF VIRTUAL GEOBOARD-BASED LEARNING MEDIA ON ELEMENTARY SCHOOL STUDENTS’ SPATIAL THINKING - Astriani, Linda; Andini, Nur Meilia (KALAMATIKA Jurnal Pendidikan Matematika, 2025)
This research was motivated by the observation that students had low ability in visualizing flat shapes, particularly when solving problems related to plane geometry. This study aimed to investigate the effect of virtual geoboard-based manipulative learning media on the spatial thinking skills of fourth-grade students. This research employed a quantitative approach with a posttest-only control group design and purposive sampling as the sampling technique. The samples consisted of two classes from all fourth-grade classes at SDN Pondok Aren 02: the experimental class, which used virtual geoboard media (Class IVB, 32 students), and the control class, which did not use virtual geoboard media (Class IVC, 26 students). Both groups were confirmed to have a normal distribution and to originate from a homogeneous population. The results of the study showed that: 1) the use of virtual geoboard media had a significant effect on students' spatial thinking skills. 2) There was a notable difference in the average posttest scores between the experimental and control classes, demonstrating the strong impact of virtual geoboard media on enhancing students' spatial thinking.